A Rare Case of Signet Ring Cell Colon Cancer Presenting as Adult Colorectal Intussusception - Gaskin, D. A.; Reid, A.; O’Shea, M.; Gaskin, P. S. (Case reports in pathology, 2022)
Signet ring cell carcinoma of the rectum is rare and typically presents with advanced disease. We report a case of a 68-year-old man who presented with left lower quadrant pain and was found to have signet ring cell carcinoma with intussusception. This case is unusual because of its polypoid growth pattern and apparent early pathological stage. We discuss the differential diagnoses and prognosis.